Breast tuberculosis: A forgotten diagnosis - S. Oucharqui (Elsevier, 2021)
Breast tuberculosis is a rare entity even in endemic countries. It is often considered as a diagnostic conundrum given the non-specific clinical and imaging characteristics. Therefore, the definitive diagnosis is based on the identification of bacilli by microbiological or histopathological examination. We report the case of a 52-year-old woman, with a 2-month history of a painful lump of the left breast. The imaging features were consistent with a breast abscess. The purulent collection was aspirated and a tuberculous mammary abscess was diagnosed by molecular biology (GeneXpert). Through this observation, we discuss the clinical, radiological and biological signs by highlighting the contribution of molecular biology in the rapid management of this rare pathology.